DEVELOPMENT OF MEDIA LITERACY AND COMMUNICATION SKILLS BY MEANS OF DIGITAL STORYTELLING IN JAPAN - Lyubov V. Gutor; Pavlo A. Sodomora; Oleh H. Vasylenko; Halyna I. Zalutska (Інформаційні технології і засоби навчання)
The research substantiates Japanese experience of media literacy and oral communication skills development by digital storytelling (DST); reveals theoretical background and current practical application of DST in higher education of Japan. DST has significant advantages as an individual- and situation-oriented tool of oral communication as well as the instrument of psychological and learning influence on society. It is continuously implemented into Japanese educational and social practice. Famous universities of Japan initiate and realize scientific and academic projects, extending communication connections of Japanese population, improving their skills of critical thinking and argumentation, developing desires and abilities to communicate freely, fluently, confidently and persuasively.